1981
DOI: 10.1037/0022-3514.40.6.1039
|View full text |Cite
|
Sign up to set email alerts
|

Altruism as hedonism: Helping and self-gratification as equivalent responses.

Abstract: An experiment was conducted to test the proposition that for adults, altruism and self-gratification are functional equivalents. It was predicted on the basis of this proposition that the effects of mood state on altruism would be parallel to the effects of mood on self-gratification. In support of this prediction, three separate findings from the mood-altruism literature were paralleled in the present study's investigation of the effects of mood on self-gratification. Specifically, it was found that (a) self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(127 citation statements)
references
References 20 publications
4
118
0
5
Order By: Relevance
“…having gained a moral license, leads to a boost in one's self-concept (Khan and Dhar (2006). This affirmative boost puts individuals in a positive mood, which in turn increases an individual's tendency for self-gratification seeking (Baumann et al 1981). Arguably, pro-social behavior, which benefits society, can be seen as self-rewarding as well.…”
Section: Type Of Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…having gained a moral license, leads to a boost in one's self-concept (Khan and Dhar (2006). This affirmative boost puts individuals in a positive mood, which in turn increases an individual's tendency for self-gratification seeking (Baumann et al 1981). Arguably, pro-social behavior, which benefits society, can be seen as self-rewarding as well.…”
Section: Type Of Decisionmentioning
confidence: 99%
“…Views on morality differ across cultures (Pew Research Center 2014), hence we assume an impact of culture on moral licensing. Building on self-gratification theory (Baumann et al 1981), we suggest that moral licenses have a bigger impact on self-rewarding than on society-related decisions. Due to the phenomenon of moral cleansing (Conway and Peetz 2012), contrasting a moral licensing group with a neutral control group should result in smaller effect sizes than the comparison with a group whose participants performed an immoral task.…”
Section: Conceptualization Of Moderatorsmentioning
confidence: 99%
“…The possibility that a prosocial orientation is motivated by the anticipation of positive affect (pleasure) is acknowledged by virtually all scholars in the field (e.g., Archer, Diaz-Loving, Gollwitzer, Davis, & Foushee, 1981;Batson, 1987;Baumann, Cialdini, & Kenrick, 1981;Cialdini et al, 1997;Harris, 1977;Schaller & Cialdini, 1988;Smith, Keating, & Stotland, 1989;Weiss, Buchanan, Alstatt, & Lombardo, 1971;Williamson & Clark, 1989). Following this research, we call the first motivation that underlies the prosocial personality ''pleasure based prosocial motivation''.…”
Section: Pleasure and Pressure Based Prosocial Motivationmentioning
confidence: 99%
“…Alongside topics such as developing strengths, positive emotion, and resilience, recent movements within positive psychology have also highlighted additional fruitful constructs for study in outdoor contexts, such as giving. For example, studies have found that other-giving emotions and behaviours performed regularly are associated with feelings of happiness and life satisfaction (Sheldon & Lyubomirsky, 2004), relieving negative states such as sadness and distress (Baumann, Cialdini, & Kendrick, 1981;Midlarsky, 1991), and promoting greater wellbeing, health, and longevity (Post, 2005;Schwartz, Keyl, Marcum, & Bode, 2009), where giving appears to be as potent as that of receiving for the giver (Brown, 2003;Brown, Nesse, Vinokur, & Smith, 2003;Schwartz et al, 2009). This research base supports evidence from service-learning approaches which have found that students exposed to meaningful community service experience increased empathy, altruism, and academic outcomes (Billig, 2000;Scales, Roehlkepartain, Neal, Kielsmeier, & Benson, 2006).…”
Section: Positive Psychology and Outdoor Educationmentioning
confidence: 99%